2015
DOI: 10.1016/j.lfs.2015.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the monoamine system in antidepressant-like properties of 4-(1-phenyl-1h-pyrazol-4-ylmethyl)-piperazine-1-carboxylic acid ethyl ester

Abstract: In conclusion, PPMP demonstrates antidepressant-like effect that involve both serotonergic and catecholaminergic systems without inhibition of MAO activity. PPMP administration increased the hippocampal levels of BDNF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Therefore, this paper describes some of the central pharmacological activities of many drugs that are piperazine derivatives used as antipsychotic, antidepressant and anxiolytic drugs as well as other types of drugs that act on the central nervous system. Additionally, the research group of Laboratório de Farmacologia de Produtos Naturais e Sintéticos/UFG has studied the neuropharmacological activity of some piperazine derivatives (LQFM008, LQFM032 and LQFM180) and demonstrated that these compounds possess anxiolytic‐ and antidepressant‐like activity involving mainly the serotonergic pathway .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this paper describes some of the central pharmacological activities of many drugs that are piperazine derivatives used as antipsychotic, antidepressant and anxiolytic drugs as well as other types of drugs that act on the central nervous system. Additionally, the research group of Laboratório de Farmacologia de Produtos Naturais e Sintéticos/UFG has studied the neuropharmacological activity of some piperazine derivatives (LQFM008, LQFM032 and LQFM180) and demonstrated that these compounds possess anxiolytic‐ and antidepressant‐like activity involving mainly the serotonergic pathway .…”
Section: Introductionmentioning
confidence: 99%
“…Gladino et al. reported 4‐(1‐phenyl‐1 H ‐pyrazol‐4‐ylmethyl)‐piperazine‐1‐carboxylic acid ethyl ester (PPMP, 52 ), having antidepressant activity via monoamine systems [101] . The results from TST and FST studies revealed that 52 (Figure 20) possesses potential antidepressant activity by serotonergic and catecholaminergic systems.…”
Section: Recent Advancements In Piperazine Derivatives As Antidepressantsmentioning
confidence: 99%
“…5 The monoaminergic hypothesis, the depleted the level of serotonin, noradrenaline, and dopamine in the central nervous system which induces depression. 6 The hypothesis is unable to fully explain the depression complexity and delay in therapeutic effect of antidepressant drugs, other complementary theory such as neurotrophic hypothesis is developed, which postulates that low levels of neurotrophic factors mainly the brain derived neurotrophic factor (BDNF) is associated with depression. 6 Plant species plays a very important role for the development of medicines.…”
Section: Introductionmentioning
confidence: 99%
“…6 The hypothesis is unable to fully explain the depression complexity and delay in therapeutic effect of antidepressant drugs, other complementary theory such as neurotrophic hypothesis is developed, which postulates that low levels of neurotrophic factors mainly the brain derived neurotrophic factor (BDNF) is associated with depression. 6 Plant species plays a very important role for the development of medicines. Native peoples had good knowledge about the medicinal herbs.…”
Section: Introductionmentioning
confidence: 99%